Highly selective hydrogenation of halogenated nitroarenes over Ru/CN nanocomposites by in situ pyrolysis. (1st July 2020) - Yue, Shengnan; Wang, Xueguang; Li, Shaoting; Sheng, Yao; Zou, Xiujing; Lu, Xionggang; Zhang, Chunlei
Abstract : Halogenated nitroarenes were high selectively hydrogenated on Ru/CN catalyst prepared by in situ pyrolysis. Abstract : A highly chemoselective and recyclable ruthenium catalyst for the hydrogenation of halogenated nitroarenes has been prepared via the simple in situ calcination of a mixture of melamine, glucose and ruthenium trichloride. Superfine Ru particles (2.3 ± 0.3 nm) were obtained and highly dispersed in the nitrogen-doped carbon matrix. The Ru/CN catalyst smoothly transforms a variety of halogenated nitroarenes to the corresponding haloanilines with high intrinsic activity ( e.g. TOF = 1333 h −1 for p -chloronitrobenzene) and selectivity of more than 99.6%. Furthermore, through an analysis of the products in the reaction process, it was concluded that there are two parallel reaction pathways (a direct pathway and an indirect pathway) for the hydrogenation of aromatic nitro compounds over the Ru/CN catalyst, and the direct pathway was proved to be dominant in catalyzing the intermediates.